2014
DOI: 10.1371/journal.pone.0099450
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid Receptor 2-63 QQ Variant Is Associated with Persistently Normal Aminotransferase Serum Levels in Chronic Hepatitis C

Abstract: Background and AimTo evaluate in anti-HCV-positive patients the clinical impact of the rs35761398 variant of the CNR2 gene leading to the substitution of Gln (Q) of codon 63 of the cannabinoid receptor 2 (CB2) with Arg (R).Patients and Methods253 consecutive anti-HCV-/HCV-RNA-positive patients were enrolled, of whom 53 were HCV carriers with persistently normal ALT (PNALT group) and 200 had a history of steadily abnormal serum ALT values (abnormal ALT group). All patients were naive for antiviral therapy and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“…It has been demonstrated that QQ variants are associated with persistently normal aminotransferase serum levels in CHC. Association of QQ variants and persistently normal aminotransferase serum levels in CHC could result from robust inhibition of the T cells with QQ variants activation and the subsequent less active immune response to infected hepatic cells [Coppola et al, 2014b]. These results suggest that CB1 receptor activation may contribute to liver disorders in HCV infection, but that CB2 receptors produce different effects according to their variant.…”
Section: Hepatitis Cmentioning
confidence: 89%
“…It has been demonstrated that QQ variants are associated with persistently normal aminotransferase serum levels in CHC. Association of QQ variants and persistently normal aminotransferase serum levels in CHC could result from robust inhibition of the T cells with QQ variants activation and the subsequent less active immune response to infected hepatic cells [Coppola et al, 2014b]. These results suggest that CB1 receptor activation may contribute to liver disorders in HCV infection, but that CB2 receptors produce different effects according to their variant.…”
Section: Hepatitis Cmentioning
confidence: 89%
“…In our previous study performed on 253 anti-HIV negative subjects with HCV chronic infection the CB2-63 QQ variant and an older age were found to be independently associated with an asymptomatic, inactive condition characterized by persistently normal alanine-aminotransferase (PNALT) values at a two-monthly determination for 18 months or more [ 50 ], whereas in a subsequent investigation on 169 anti-HIV-negative patients with HCV-related chronic hepatitis, the CB2-63 QQ variant was associated with more severe liver necroinflammation [ 53 ]. Based on the observation that CB2-mediated inhibition of T-cell proliferation has been shown to be normal in T cells deriving from QQ subjects and reduced two-fold in T cells from subjects with the RR homozygous variant [ 54 ], these associations were interpreted as the result of differences in the strength and duration of the inhibition of the T cells expressing CB2-63 QQ or CB2-63 RR and of the consequent lesser or more vigorous immune response against infected hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…All primers were chosen using Primer3 software ( http://primer3.sourceforge.net/ ). This procedure had been used in previous investigations [ 49 , 50 ].…”
Section: Methodsmentioning
confidence: 99%
“…Ninety-nine consecutive Italian patients followed up by three Liver Units in Naples, Southern Italy, that have cooperated for years in several clinical investigations [25,29], entered the study at the time they underwent their first liver biopsy from July 2009 to December 2013 for asymptomatic chronic hepatitis B. All patients were HBsAg positive and were naive for antiviral therapy.…”
Section: Methodsmentioning
confidence: 99%
“…To assess liver steatosis, we used a homemade scoring system obtained with a partial modification of Kleiner's scoring system for NAFLD [32]. Briefly, steatosis was defined starting from score [0; score 1 identifies the presence of fatty deposition in 1-10 % of hepatocytes, score 2 in 11-31 %, score 3 in 31-60 %, and score 4 in [60 % [25,29]. Score 3 and score 4 were referred as severe steatosis.…”
Section: Methodsmentioning
confidence: 99%